Intergenerational Trauma and Family Resilience: Exploring the Role of Family Counseling in Breaking the Cycle of Violence tnd Abuse - Mujahidah, Mujahidah; Zulaekah, Zulaekah; Cha, Som (Yayasan Minang Darussalam, 2024)
Intergenerational trauma and family resilience are critical issues that significantly impact mental health and social dynamics. This study investigates the transmission of trauma across generations and its role in perpetuating cycles of violence and abuse within families. By examining the effectiveness of family counseling as an intervention, the research seeks to identify strategies that can disrupt these harmful patterns. Utilizing a qualitative methodology, data were gathered through in-depth interviews with therapists and families affected by intergenerational trauma. The results reveal that family counseling serves as a vital tool not only for conflict resolution but also for fostering open communication, empathy, and understanding among family members. Participants reported that counseling facilitated the development of healthy coping mechanisms and strengthened family bonds, enhancing overall resilience. Furthermore, the study highlights the importance of culturally sensitive approaches in counseling to address the specific needs of families from diverse backgrounds. These findings underscore the potential of family counseling to promote healing and recovery, effectively breaking the cycle of violence and abuse. By providing a supportive environment, families can cultivate resilience, ultimately leading to healthier relationships and improved mental well-being for future generations.